Effect of a continuity of midwifery care model that used a respectful maternal care framework in Korea: a non-randomized study - Jeong, Geumhee; Kim, Hyun Kyoung; Bang, Uri (Frontiers in Public Health, 2025)
AimThis study evaluated “Team-Mamas,” a continuity of midwifery care intervention that used a respectful maternity care framework during the antenatal, labor, and postpartum periods. The research aimed to assess the impact of intervention on birth outcomes, birth satisfaction, birth experience, and maternal function.Participants and settingThis study employed a non-equivalent control group post-test design. The midwife companion program offered services including natural childbirth education, prenatal healthcare, birth rehearsal, childbirth support, infant care, and postpartum education and counseling. This program provided continuous support by midwives from the 28th week of gestation until 14 days after birth. There were 65 participants from 3 cities in Korea from March to November, 2023.ResultsThe intervention led to lower frequencies of episiotomy (p < 0.001), oxytocin augmentation (p = 0.005), epidural anesthesia (p = 0.007), and analgesic use (p < 0.001), as well as higher breastfeeding rates at 1 week (p = 0.012) and 4 weeks (p = 0.004) postpartum in the experimental group compared to the control group. Both birth satisfaction (p < 0.001) and birth experience (p < 0.001) scores were higher in the experimental group compared to the control group. No statistically significant differences were found between the two groups regarding neonatal birth weight (p = 0.346) and maternal function (p = 0.067).ConclusionMothers experienced satisfactory and safe birth outcomes when supported by a continuity of midwifery care intervention. We suggest promoting positive birth outcomes and experiences through integrated support that honors the dignity of mothers throughout pregnancy, labor, birth, and the postpartum period.Clinical trial registrationIdentifier (KCT0008956) in the Korean Clinical Research Information Service.